PERGESERAN DAN PERKEMBANGAN TERMA MUTAWATTIR DALAM STUDI HADIS - Afwadzi, Benny (Madura State Islamic Institute (Institut Agama Islam Negeri (IAIN) Madura), 2017)
This article discusses about displacement and development of mutawatir in hadith studies. The author finds that the term did not recognized in classical period of hadith studies and clearly introduced by Ibnu Salah (7 H.). The term was developed significantly by Ibnu Hajar (9 H.). After the emergence of Ibnu Hajar, mutawatir hadith became popular discourse and discussed by most of scholars. In this article, the author concludes that there are several displacements and developments, first, mutawatir hadith initially form a part of masyhur hadith and then standed independently on its afters works. Second, the number of mutawatir hadith were added significant, on its beginning not available, then said available one, and then developed continually. Third, the categorization of mutawatir hadith was added from one period to other period, lafzi, ma’nawi, and ‘amali. Fourth, in the early recognition, the numbers of transmitter ranging on fourty persons, and then fluctuated until number of ten persons becomes the popular opinion.